Railroad Hank - Moser, Lisa (Random House Children's Books, 2012)
On his way to visit Granny Bett, who is feeling blue, Railroad Hank stops at the farms of several friends and, misunderstanding their offers to help, winds up with a trainload of crazy cargo.